Intelligent algorithm for trapezoidal interval valued neutrosophic network analysis. Issue 2 (3rd April 2020) - Broumi, Said; Nagarajan, Deivanayagampillai; Lathamaheswari, Malayalan; Talea, Mohamed; Bakali, Assia; Smarandache, Florentin
Abstract : The shortest path problem has been one of the most fundamental practical problems in network analysis. One of the good algorithms is Bellman‐Ford, which has been applied in network, for the last some years. Due to complexity in the decision‐making process, the decision makers face complications to express their view and judgment with an exact number for single valued membership degrees under neutrosophic environment. Though the interval number is a special situation of the neutrosophic, it did not solve the shortest path problems in an absolute manner. Hence, in this work, the authors have introduced the score function and accuracy function of trapezoidal interval valued neutrosophic numbers with their illustrative properties. These properties provide important theoretical base of the trapezoidal interval valued neutrosophic number. Also, they proposed an intelligent algorithm called trapezoidal interval valued neutrosophic version of Bellman's algorithm to solve neutrosophic shortest path problem in network analysis. Further, comparative analysis has been made with the existing algorithm.